PEMEROLEHAN BAHASA ANAK USIA 4-5 TAHUN MELALUI MEDIA AMPLOP BERGAMBAR : KAJIAN PSIKOLINGUISTIK - Shinta Aprilia; Chindy Aulia; Faiqotul Hasanah; Maulida Putri Amelia; Hodairiyah Hodairiyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to conduct an in depth examination of the language acquisition process in 4 to 5 year old children through an intervention using illustrated envelopes at the At-Taufiqiyah Early Childhood Education Center from a psycholinguistic perspective. Specifically, this study examines how the cognitive aspects and children’s interest, triggered by this tactile-visual medium, can stimulate their syntactic and morphological components. The research method used was descriptive qualitative. Data collection was conducted through direct testing using illustrated envelope media with 7 students at the At-Taufiqiyah Early Childhood Education Center. Data analysis focused on linguistic units specifically phrases and words produced by the children as they described the pictures. The results of the study indicate that 4 to 5 year-old children have consistently moved beyond the holopraxic stage and are in a mature multi-word stage, with the ability to produce 2 to 4 words containing Subject (S) and Predicate (P) structures. Based on psycholinguistic theory, children use the word “Person” as a Pivot Word (a fixed key word) and descriptions of surrounding activities as Open Words (variable words), such as the S+P+O construction (“Person washes hands”). Translated with DeepL.com (free version). Morphologically, children’s language production is dominated by lexical morphemes without affixes (informal spoken language); however, some 5-year olds have already begun to show consistent use of formal affixation in the form of nasal prefixation (meN-), which they have acquired from their social environment.